Varicocoele among 1 300 000 Israeli adolescent males: time trends and association with body mass index. (22nd August 2013) - Rais, A.; Zarka, S.; Derazne, E.; Tzur, D.; Calderon‐Margalit, R.; Davidovitch, N.; Afek, A.; Carel, R.; Levine, H.
Summary: Scarce data are available on epidemiology of varicocoele, the most common surgically correctable cause of male infertility. The objectives of this study were to evaluate the association between body mass index (BMI) and varicocoele and to assess trends in prevalence over time. We conducted a nationwide population‐based long‐term (1967–2010) study among 1 323 061 Israeli adolescent males using data from mandatory medical examination. BMI was grouped into underweight, normal weight, overweight and obese categories by percentiles adjusted for age in months and by further classification to five categories within normal weight. Univariable and multivariable logistic regression models were constructed, adjusting for possible confounders. Varicocoele prevalence ( N  = 47 398) increased during the study period from 1.6% for the 1950–1954 birth cohort to 4.6% for the 1990–1993 birth cohort, with the steepest rise in the normal weight group. Varicocoele unadjusted rates were highest (4.1%) among underweight and lowest (1.6%) among obese. In a multivariable model, adjusted for birth cohort, height, age and socio‐demographic factors, we found a decreased risk for varicocoele in the overweight group [odds ratio (OR) = 0.51, 95% confidence interval (CI): 0.49, 0.54] and the obese group (OR = 0.34, 95% CI: 0.32, 0.37), compared with the normal weight group. Within the normal weight group, a monotonic inverse association between BMI percentile and varicocoele was observed, most notable among 75–84.9 percentile compared to 25–49.9 percentile (OR = 0.65, 95% CI: 0.63, 0.68). In conclusion, varicocoele is common among adolescents in Israel, and its prevalence had increased in recent decades, providing clues to direct further andrological research on the role of modern lifestyle and environment in the aetiology of varicocoele. BMI, across percentiles, was found to be monotonically inversely associated with varicocoele, thus directing research and clinical efforts.